The Patient's Role in Patient Safety: Starting Early Patients who are involved in their own care get the best outcomes - Ilene Corina (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2020)
Articles and studies have reported this for years. But how do we make this happen and what does it mean? People don't usually plan to become patients just as they don't plan on getting into a car accident. Still we buckle up in case someone causes an accident, not because they are bad drivers but because accidents and mistakes can happen. We teach young people to "stop, drop and roll" in case they catch on fire. But how often does that happen? We teach people how to do CPR or Cardiopulmonary Resuscitation before they witness someone having a heart attack, not as it's happening.